2007
DOI: 10.1002/cne.21504
|View full text |Cite
|
Sign up to set email alerts
|

Long‐distance corticocortical GABAergic neurons in the adult monkey white and gray matter

Abstract: A subgroup of GABAergic neurons has been reported to project over long distances in several species. Here we demonstrate that long-distance cortically projecting nonpyramidal neurons occur in monkeys in both white and gray matter. Nonpyramidal neurons were first identified morphologically. Visualization of Golgi-like details was achieved by retrograde infection from injections of an adenovirus vector, producing enhanced green fluorescent protein (EGFP) under control of a neuron-specific promoter. Injections in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
127
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 233 publications
(356 reference statements)
8
127
2
Order By: Relevance
“…Previous studies reported the presence of longrange GABAergic projection neurons in the white matter. Most of these cells express nNOS, NPY, and somatostatin (Tomioka et al, 2005;Higo et al, 2007Higo et al, , 2009Tomioka and Rockland, 2007;Tamamaki and Tomioka, 2010) and are not identical with the cell population characterized in this study. Interestingly, some EGFP-positive WMICs have dendrites in the striatum and hippocampus and axons reaching into the cortex.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Previous studies reported the presence of longrange GABAergic projection neurons in the white matter. Most of these cells express nNOS, NPY, and somatostatin (Tomioka et al, 2005;Higo et al, 2007Higo et al, , 2009Tomioka and Rockland, 2007;Tamamaki and Tomioka, 2010) and are not identical with the cell population characterized in this study. Interestingly, some EGFP-positive WMICs have dendrites in the striatum and hippocampus and axons reaching into the cortex.…”
Section: Discussioncontrasting
confidence: 67%
“…Thus, the fluorescently labeled population comprised two cell groups, i.e., cells with dendrites and axons extending beyond the white matter boundaries with preferential arborization in lower cortical layers, but also in the hippocampus and striatum (type 1), and smaller cells located in the lower third of the corpus callosum with processes confined by and large to the white matter (type 2). WMICs with axons projecting to the cortex were described previously (Meyer et al, 1991;Clancy et al, 2001;Tomioka and Rockland, 2007). Most EGFP-positive WMICs had comparably small axonal arbors and do not meet the criteria of long-range GABAergic projection neurons with an axonal arbor extending Ͼ1.5 mm into the cortex (Tomioka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, in monkeys and in the glutamate decarboxylase 67 kDa (GAD67)-GFP knock-in mouse, in which neurons normally expressing the GABA-synthesizing enzyme GAD67 (also known as GAD1) are labelled with GFP, GABAergic interneurons in subplate also form long-distance projections 87,88 . It is yet to be determined how many of these connections are temporary.…”
Section: Barrel Fieldmentioning
confidence: 99%
“…In humans, subplate neurons express GABA (Schiffmann et al 1988;Yan et al 1992;Masood et al 1993;Zecevic & Milosevic, 1997), vesicular GABA transporter, a potassium ⁄ chloride co-transporter (KCC2) (Bayatti et al 2008), various glutamate receptors (Lee & Choi, 1992;Andersen et al 1995;Ritter et al 2001;Talos et al 2006), AChE (Kostovic & Rakic, 1980;Kostović et al 1981;Kostović, 1984), and nicotinic acetylcholine receptors (Schrö der et al 2001). In the monkey, subplate neurons also express GABA (Huntley et al 1988;Meinecke & Rakic, 1992;Tomioka & Rockland, 2007) and GABA-A receptors (Huntley et al 1990;Meinecke & Rakic, 1992). GABA-positive fibres and somata have also been detected in the cortical white matter of adult monkeys (Hendrickson et al 1981;Schwartz et al 1988).…”
Section: Neurochemical Diversitymentioning
confidence: 99%